Silk fibroin, gelatin, and human placenta extracellular matrix-based composite hydrogels for 3D bioprinting and soft tissue engineering. - Schneider, Karl Heinrich.; Goldberg, Benjamin J; Hasturk, Onur.; Mu, Xuan.; Dötzlhofer, Marvin.; Eder, Gabriela.; Theodossiou, Sophia.; Pichelkastner, Luis.; Riess, Peter.; Rohringer, Sabrina.; Kiss, Herbert.; Teuschl-Woller, Andreas H; Fitzpatrick, Vincent.; Enayati, Marjan.; Podesser, Bruno K; Bergmeister, Helga.; Kaplan, David L (Tufts University. Tisch Library., 2023)
Keywords: Attenuated total reflection, Deionized water, Dulbecco's Modified Eagle Medium, 1-ethyl-3-(-3-dimethylaminopropyl) carbodiimide hydrochloride, Fetal bovine serum, Free reversible embedding of suspended hydrogels, Fourier transform infrared spectroscopy, Tyramine-substituted gelatin, hematoxylin and eosin, Hydrogen peroxide, Hydrochloric acid, Hydroxyethyl)piperazine-1-ethane- sulfonic acid, Human dermal fibroblasts, neonatal, Human placenta chorion extracellular matrix, Human placenta extracellular matrix, Horseradish peroxidase, International-Units, Kilodalton, Lithium bromide, 2-(N-Morpholino) ethanesulfonic acid, Molecular weight cutt off, N-hydroxysuccinimide, Phosphate-buffered saline, Polydimethylsiloxane, Polyethylene glycol, Poly(2-hydroxyethyl methacrylate), Polylactic acid, 60 minutes boiled silk, Silk fibroin, Silk - Gelatin - ECM.; Springer Open.